Reconstruction of symbolic representations as a mechanism for harmonising sensory-emotional states in psychological counseling - BABYCH, Roman; LATYNINA, Svitlana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
depends on two opposing demands. On the one hand, the consultant must adhere to a specific action strategy to guarantee achieving the desired outcome. On the other hand, the client must be highly engaged in the problem-solving process and have the freedom for creative work and personal development.The article aims to describe a technology for harmonizing sensory-emotional states based on the principles of a system-thinking-activity approach to psychological counseling.Our aim is to combine the consultant's strategic orientation and the client's creative freedom within one technology. We used the scheme of psychological counseling in a system-thinking-activity approach and the principles of its implementation as a method of configuration. The object of psychotechnical work is the symbolic representations of sensory-emotional states, and the psychotechnical tools used are Clean Language and Symbolic Modeling.The article examines the action strategy of a consultant psychologist and discusses the principles, foundations, and mechanisms of psychological counseling within the system-thinking-activity approach. Methods of their implementation within the technology are also considered. Particular attention is given to the features of the psychoactive metaphor as a sign-symbolic representation of sensory-emotional states and the means of working with it.The study investigates the scheme that allows the consultant to manage the process of exploring the client's own symbolic space. It describes reflective transitions that both the client and the consultant go through during problematization and the development of schemes for organizing thought and action. It also includes a detailed description of one of the tactics for reconstructing symbolic representations, along with an example of its practical implementation.
Keywords: psychotechnique; strategy; counseling; representation; metaphor; reflection